Afetividades distantes, pinturas aproximativas - Santos Junior, Antonio José dos (2020)
This investigation aims at the realization of a series of ten paintings, whose poetics highlights the reconstruction of personal memories. The work was formulated starting from stories on particular objects of people, family members or affectively significant friends, who were linked to the artist in different periods and places. These individuals descriptions of their memories of these objects, broaden and reframe the meaning of the word familiar, when applied to the objects themselves. The pictorial experiments were produced based only on subjective stories sent to the artist via email or social networks. This procedure made it possible to materialize the invisible image, starting from its recreation. The research was developed through poetics and the use of “social poetic practice”, a term addressed by the author. For the exhibition of the works, a wooden monocle was used, which facilitates the mediation of these pictorial experiments, establishing a distance between the painting and the spectator, creating a fundamental distance between the lived time and the present time, now resignified, as well as discussions about time and the dichotomy between distance and approximation. The involvement of individuals in this poetic action has potentialized the research and reflection on the creation of new images in contemporary times.